Comparison of the effects of desmethylimipramine on behavior in the forced swim test in peripubertal and adult rats - Pechnick, Robert N. (2008)
Although there are similarities in the clinical presentation of adolescent and adult depression, there are differences in the biological correlates and the responses to pharmacologic treatment. Selective serotonin reuptake inhibitor-type antidepressants are efficacious, but tricyclic antidepressants have no or limited efficacy in treating adolescent patients. The forced swim test (FST) is a widely accepted animal model used to screen drugs for antidepressant activity. It is not known whether tricyclic antidepressants produce differential effects in peripubertal and adult rats, as is found in adolescent and adult humans. The objective of the study was to test the hypothesis that the tricyclic antidepressant desmethylimipramine (DMI) would show efficacy in the FST in adult, but not in peripubertal, rats. Thirty-day-old (peripubertal) and 112-day-old (young adult) rats were pretreated with saline or DMI and subjected to the FST. DMI reduced the amount of floating behavior and increased the amount of climbing behavior in both peripubertal and adult rats. Thus, the tricyclic antidepressant DMI has antidepressant-like activity in peripubertal rats in the FST. Owing to the discrepancy between the preclinical and clinical data, the predictive validity of the FST might need to be reevaluated across different age groups.